Environmental drivers of growth in massive Porites corals over 16 degrees of latitude along Australia's northwest shelf. (16th December 2015) - Lough, J. M.; Cantin, N. E.; Benthuysen, J. A.; Cooper, T. F.
Abstract: Sustained calcification is fundamental for maintaining tropical coral reef ecosystems which are under increasing pressure from global and local changes to the marine environment. Annual density bands in massive corals provide a robust means to retrospectively monitor growth and identify the environmental drivers. We present Porites growth characteristics for 60 coral cores from 18 reef sites and five environmental regions off Western Australia (WA) over the period 1950–2008. This remote region encompasses diverse coral reef ecosystems and is an economically important natural resource hub. Despite high variability, average calcification is highest in the offshore shelf reefs and lowest in the most southerly reefs. The primary environmental drivers of these spatial variations are annual and winter minimum sea surface temperature (SST) and annual winter minimum photosynthetically active radiation. Average growth characteristics for WA reefs are comparable to those of Australia's Great Barrier Reef. Calcification rates at the two most southerly WA reefs are anomalously high, which may be due to the unusual environmental conditions generated by the Leeuwin Current. Variable rates of SST warming across the 18 reefs are, however, changing the strength of the relationship between SST and calcification. We found no evidence to support the contention that annual density banding is driven by environmental seasonality. Retrospective monitoring of growth rates provides a critical tool for both assessing coral growth responses to ongoing rapid climate change and possible responses to increasing anthropogenic pressures related to natural resource development in the region.